Apologies from the Editorial Board for the Unauthorized Use of Another Author’s Article - Editorial Board (University of Belgrade, 2010)
The Editorial Board of Etnoantropoloski problemi / Issues in Ethnology and Anthropology would like to inform the public that the article: “Who’s Singing over There? Transnationalism in Post-Yugoslav Popular Music and Its Boundaries“ by Marijana Mitrović, published in Issues in Ethnology and Anthropology Vol. 4,  Is. 3 for the year 2009, pp. 117-143, was written with the unauthorized use of Catherine Baker’s study “The Politics of Performance: Transnationalism and its Limits in Former Yugoslav Popular Music 1999-2004” published in Ethnopolitics Journal Vol. 5, Is. 3 September 2006 on pages 275 - 293. The aforementioned unauthorized use consists of plain out copying of the text without use of any citational methods, or other types of crediting.